To Study The Impact Of Leadership Styles On Organisational Performance And Employee Satisfaction Among Employee Of It Industries In Ahmedabad - Mahida Dhruvika; Rathi Darshan; Jignesh Vidani (Journal of Advanced Research in Economics and Business Management, 2025)
This study is expected to identify the relationship between leadership styles and organization performance and general employee satisfaction in IT firms in Ahmedabad. In this study, both quantitative and qualitative data were gathered and analyzed through a mixture of the two methods. For this study, semi-structured interviews were administered to 15 participants, and 200 employee participants were asked to complete a survey. The results of the study show that there is a positive relationship between transformational leadership and both perceived levels of employee satisfaction and overall organizational performance. On the other hand, the laissez-faire leadership style was associated with negative outcomes, and the transformational leadership style yielded moderate outcomes. As a result, the current study suggests that Ahmedabad’s IT companies should adopt transformational leadership practices as a way of improving employee satisfaction and organizational performance. The current work enhances the current literature on the effects of leadership beliefs on employee engagement and organizational outcomes in the IT sector.